A study of profile of contact dermatitis in housewives with reference to vegetables, soaps and detergents - Malhotra, Vidushi; Dogra, Alka; Gupta, Sunil Kumar; Kaur, Sandeep (International Journal of Research in Dermatology, 2018)
Background: Contact dermatitis in housewives is a common dermatological problem as almost all housewives have to handle vegetables, fruits, soaps and detergents. The purpose of this project was to study etiologic profile of contact dermatitis occurring in housewives. Methods: One hundred housewives, clinically diagnosed as having contact dermatitis, were randomly selected for the study. Each patient was then subjected to patch testing using the Indian standard battery and certain indigenously prepared antigens i.e. vegetables, soaps and detergents. The first reading was taken 60 minutes with second reading at 96 hours. Reading equal to or more than 1+ was considered to be a positive test. Results: Majority patients were in the age group of 20-30 years. Morphological diagnosis was wear and tear dermatitis in 43%, discoid eczema (19%), fingertip eczema (16%), hyperkeratotic (15%) and pompholyx (7%). Nickel sulphate was found to be the commonest allergen (19%) followed by para-phenylenediamine (8%), fragnance mix (7%), Balsam of Peru (6%), parthenium (6%) and cobalt (5%). Amongst vegetables, the commonest culprit was garlic. Allergic reaction to detergents was positive in 13% patients. Forty-four percent of the cases tested positive to the suspected allergen whereas 31% patients tested positive for allergens not initially suspected of causing contact dermatitis in them. Conclusions: Thus patch testing is an important tool in establishing the cause of allergic contact dermatitis of the hands in housewives in whom the hand eczema is multifactorial. This enables the correct etiological diagnosis and proper management of housewives with hand dermatitis.